Mobile Phones and Financial Services in Developing Countries : A Review of Concepts, Methods, Issues, Evidence and Future Research Directions /: A Review of Concepts, Methods, Issues, Evidence and Future Research Directions. (2009) - Duncombe, Richard; Boateng, Richard, 1979-
No abstract available